Three Essays on Firm-Worker Separations - Sweetman, Arthur L. (My University, 1996)
Three aspects of a turnover in Canadian labour markets are presented. First, geographic mobility following job displacement, the permanent and involuntary loss of a job by a worker, is studied. In the Canadian Displaced Worker Survey, 17% of the men, and 9% of the women, find reemployment in a geographically distant labour market. The reemployment hazard of women in the local labour market is reduced by the presence of children, but that for men is unaffected by them. Allowing for a fixed unobserved characteristic, the probability of reemployment in each period, conditional on having not found reemployment earlier, is observed to be approximately constant for a typical person. Looking at unionism, tenure and the cost of job loss in the second essay, I estimate a union tenure-wage markup profile. A markup is the difference between each worker’s predisplacement and best alternative, or postdisplacement, wage. The profile is found to increase more quickly in the union than nonunion sector. This evidence suggests a resolution to a longstanding puzzle in the economic study of unions. In cross section union members’ return to tenure appears to be flatter than that in the nonunion sector, whereas several theories of union behaviour suggest that unions should preferentially redistribute rents to more senior members. Finally, a test of the efficient turnover view of labour markets is conducted using two recent Canadian legislative changes that reduced, and then eliminated, unemployment insurance benefits for those who quit or are dismissed for cause. The theory suggests that firms and workers jointly maximize their wealth which in this case, implies that they will relabel disentitled quitters to groups which may obtain benefits. No evidence of this is observed; however workers, especially female ones, are inhibited from quitting. This is interpreted as evidence against the efficient turnover model.
Keywords: Economics; Economics